Experimental investigation of shear band and shear strain field evolution during blanking of AA6082 sheet. (February 2019) - Sonkamble, Vijayalaxmi; Dhondapure, Prashant; Narasimhan, K; Tewari, Asim
Interrupted blanking experiments were performed to study the deformation behavior of AA6082 (T6) sheets. An intentional asymmetry was introduced by having the punch and the die of different edge radii. High-resolution microstructural montages of sheet cross-section were used to experimentally measure the shear strain field during each interrupted blanking experiment. This provided a comprehensive experimentally measured spatial–temporal shear strain field for the blanking process. The shear strain was found to be high and localized at the top and bottom surfaces of the sheet which was in contact with the punch and the die. The shear strain was observed to monotonically reduce and get diffused at the interior of the sheet. The strain distribution was also calculated by finite element simulations and found to be in good agreement with the experimentally measured strain distributions. However, the peak strains predicted by the finite element simulations were always marginally lower than those observed by the experimental observations.